Atorvastatin slows down the deterioration of inner ear function with age in mice - Syka, Josef; Ouda, Ladislav; Nachtigall, Petr; Solichová, Dagmar; Semecký, Vladimír (Neuroscience letters, 2007)
Statins have revolutionized the treatment of hypercholesterolemia due to their ability to inhibit cholesterol biosynthesis. Their immunomodulatory and anti-inflammatory effects and positive effects on the treatment of atherosclerosis and its complications are well known. Here, we describe the effects of statins on the treatment of presbycusis in C57BL/6J mice. In this strain with accelerated aging, we demonstrate that animals treated with atorvastatin (10mg/kg per day in chow diet) for 2 months showed larger amplitudes of distortion product otoacoustic emissions (DPOAE) than did the non-treated control group. This finding indicates a better survival of outer hair cell function in the inner ear of C57BL/6J mice. The observed decreased expression of intercellular and vascular adhesion molecules in the aortic wall of atorvastatin-treated animals suggests that reducing endothelial inflammatory effects may contribute to the positive effect of atorvastatin on the amplitudes of DPOAE by influencing the blood supply to the inner ear. No such beneficial effect of statins was found in apoE(-/-) mice treated with atorvastatin under the same conditions. Our results suggest that statins could also slow down the age-related deterioration of hearing in man.
Keywords: Ear, Inner; statiny; exprese genu; vztah dávky záření a odpovědi; Auditory Threshold; Gene Expression; Dose-Response Relationship, Radiation; otoakustické emise spontánní; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Acoustic Stimulation; vnitřní ucho; potrava speciální; financování organizované; stárnutí; pyrroly; Financing, Organized; zvířata; myši; Aging; myši inbrední C57BL; časové faktory; Mice; Otoacoustic Emissions, Spontaneous; myši knockoutované; Heptanoic Acids; Pyrroles; sluchový práh; mezibuněčná adhezivní molekula-1; Receptors, Vasopressin; Mice, Knockout; presbyakuze; Apolipoproteins E; Mice, Inbred C57BL; kyseliny heptylové; Animals; Intercellular Adhesion Molecule-1; receptory vasopresinů; Presbycusis; Time Factors; Food, Formulated; apolipoproteiny E; akustická stimulace